2012
DOI: 10.1074/jbc.m112.372177
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Structural Basis of Substrate Preferences in Baeyer-Villiger Monooxygenases

Abstract: Background: Bacterial steroid monooxygenase degrades progesterone. Results: The crystallographic and mutagenesis analysis outline a robust active-site scaffold, capable of performing BaeyerVilliger oxidations on chemically diverse molecules. Conclusion: This and related enzymes represent a fascinating case for the comparative evaluation of user tailored protein engineering with enzyme variants arising through evolution. Significance: These findings highlight the biocatalytic potential of Baeyer-Villiger monoox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 29 publications
1
42
0
2
Order By: Relevance
“…SAPMO converted 4-amino-and 4-nitro-acetophenone with efficiencies similar to its conversion of HAP; acetophenone, 4-hydroxypropiophenone, and benzaldehyde were less effectively converted, and cyclohexanone and acetone were not substrates (3,21). Furthermore, SAPMO did not convert progesterone, an observation that is in accordance with the substrate preference observed for PAMO (14). Finally, SAPMO exhibited a broad pH optimum, as typically observed for type I BVMOs, and in contrast to PAMO, was not heat stable (13).…”
supporting
confidence: 68%
“…SAPMO converted 4-amino-and 4-nitro-acetophenone with efficiencies similar to its conversion of HAP; acetophenone, 4-hydroxypropiophenone, and benzaldehyde were less effectively converted, and cyclohexanone and acetone were not substrates (3,21). Furthermore, SAPMO did not convert progesterone, an observation that is in accordance with the substrate preference observed for PAMO (14). Finally, SAPMO exhibited a broad pH optimum, as typically observed for type I BVMOs, and in contrast to PAMO, was not heat stable (13).…”
supporting
confidence: 68%
“…Baeyer-Villiger monooxygenases provide precedent for this phenomenon, which is known as the “sliding cofactor” model. 33,34 …”
Section: Resultsmentioning
confidence: 99%
“…From the experiment, the rate constants for H 2 O 2 elimination in S171A and S171T are approximately 1400-fold and 8-fold greater than that of the wild-type enzyme 27b and the rate 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 CHMO, 48 Arg342 and NADP + in steroid monooxygenase, 49 Arg337 and NADP + in phenylacetone monooxygenase. 50 Here, we showed that the positively charged His396 of C 2 acts as a general acid for proton-coupled electron transfer to activate O 2 .…”
Section: Discussionmentioning
confidence: 98%